Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3329/bjas.v46i2.34443
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cottage cheese from buffalo milk with different levels of papaya latex

Abstract: The study was c o n d u c t e d to standardize t h e desire level of papaya (Carica papaya) latex on quality of cottage cheese prepared from buffalo milk. Cheese sample was prepared using whole milk collected from Lal Teer Livestock Development (BD) Ltd. Dairy farm. This experiment was conducted on five treatments named as sample BC2: buffalo control; A2: 5 drops (0.16g); B2: 6 drops (0.18g); C2: 7 drops (0.21g); and D2: 8 drop (0.24g). Overall score of cheese samples, B2 was highest (91.67±0.58) and A2 was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
4
3
0
Order By: Relevance
“…The moisture content is in the line with the findings of Rana et al (2017a) but lower than the findings of Amanu (2015) and higher than that of Rana et al (2017b). Moisture in cheeses made using commercial papain and papaya latex were similar to that of rennet.…”
Section: Physicochemical Properties Of Cheese 1 Chemical Compositionsupporting
confidence: 88%
See 2 more Smart Citations
“…The moisture content is in the line with the findings of Rana et al (2017a) but lower than the findings of Amanu (2015) and higher than that of Rana et al (2017b). Moisture in cheeses made using commercial papain and papaya latex were similar to that of rennet.…”
Section: Physicochemical Properties Of Cheese 1 Chemical Compositionsupporting
confidence: 88%
“…The protein contents of all the cheeses are in line with the findings of Rana et al (2017a) but lower than that found by Rana et al (2017b). The ash contents of cheese are similar to the findings of Khan & Masud (2013), who had reported that the ash contents of cheese ranged from 2.50 to 3.20%.…”
Section: Tablesupporting
confidence: 88%
See 1 more Smart Citation
“…The ash content was found to have mild increment during the storage period for all the treatments which ranged from 0.66 to 2.50 per cent, it might be attributed to addition of calcium chloride and salt in the cottage cheese and reduction in moisture content. The findings of present study are supported by Rana et al (2017) [6] , who observed the mean ash content in cottage cheese made from buffalo milk with different levels of papaya latex to range from 2.75 to 3.79 per cent Similarly, Blanchette et al (1996) [3] reported a range of ash content from 0.97 to 1.09 per cent for cottage cheese with different fermented cream dressing.…”
Section: Resultssupporting
confidence: 88%
“…Reichert-Meissl (chiefly butyric and caproic), Polenske (mostly caprylic, capric, and lauric), and Kirschner (butyric acid) values were determined according to the method of Cd 5-40 [ 25 ]. With 5 gm of ghee sample, 20 ml of glycerol soda solution (20 ml of 500 gm/l NaOH added with 180 ml of glycerol) was added in a round-bottom flask and subsequently heated until complete saponification.…”
Section: Methodsmentioning
confidence: 99%